2011
DOI: 10.1074/jbc.m111.235754
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Small Protein Inhibitors of Human Chymotrypsin C (CTRC) Selected by Phage Display Reveal Unusual Preference for P4′ Acidic Residues

Abstract: Human chymotrypsin C (CTRC) is a pancreatic protease that participates in the regulation of intestinal digestive enzyme activity. Other chymotrypsins and elastases are inactive on the regulatory sites cleaved by CTRC, suggesting that CTRC recognizes unique sequence patterns. To characterize the molecular determinants underlying CTRC specificity, we selected high affinity substrate-like small protein inhibitors against CTRC from a phage library displaying variants of SGPI-2, a natural chymotrypsin inhibitor fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…Several studies attempted to clarify the determinants of this specificity. Phage display-selected variants of the locust-derived chymotrypsin inhibitor Schistocerca gregaria proteinase inhibitor-2 (SGPI-2) indicated that negatively charged amino acids on the primed side of the scissile peptide bond are important for CTRC recognition (16). This notion seemed in agreement with the natural preponderance of such residues in the regulatory nick sites.…”
Section: Human Chymotrypsin C (Ctrc)supporting
confidence: 68%
See 2 more Smart Citations
“…Several studies attempted to clarify the determinants of this specificity. Phage display-selected variants of the locust-derived chymotrypsin inhibitor Schistocerca gregaria proteinase inhibitor-2 (SGPI-2) indicated that negatively charged amino acids on the primed side of the scissile peptide bond are important for CTRC recognition (16). This notion seemed in agreement with the natural preponderance of such residues in the regulatory nick sites.…”
Section: Human Chymotrypsin C (Ctrc)supporting
confidence: 68%
“…Purified CTRC zymogen was activated with 50 l of immobilized trypsin (20230, Thermo Scientific) in 3-ml final volume of 0.1 M Tris-HCl (pH 8.0) for 2 h at 22°C. Concentration of active CTRC was determined using active site titration with ecotin, as described recently (16). The concentration of variants p.R29Q, p.G214R, p.S239C, and mutant p.G214M was estimated by comparing their protein band intensity with that of wild-type CTRC on Coomassie Blue-stained gels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of purified trypsinogen preparations were determined from the ultraviolet absorbance at 280 nm using the extinction coefficient 37,525 M Ϫ1 ·cm Ϫ1 SPINK1 binding assays. Binding of wild-type and p.L104P mutant human cationic trypsin to the trypsin inhibitor SPINK1 was characterized by measuring the K D value of the reaction in equilibrium, as we described previously (32,35). Trypsin concentrations were determined by titration against ecotin, and SPINK1 concentration was determined by titration against wild-type human cationic trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…The dialyzed chymotrypsinogen solutions were concentrated using a Vivaspin 20 concentrator (10-kDa molecular mass cutoff). Chymotrypsinogens were activated with trypsin, and active chymotrypsin concentrations were determined by active site titration with ecotin, as described previously (24).…”
Section: Identification Of Trypsinogens From Nmri Mouse Pancreas By Tmentioning
confidence: 99%